Simulation of one Dimensional Photoacoustic Imaging - Hussain, Mohammed A.; Jameel, Luma W. (Iraqi Journal of Laser, 2019)
The present work provides theoretical investigation of laser photoacoustic one dimensional imaging to detect a blood vessel or tumor embedded within normal tissue. The key task in photoacoustic imaging is to have acoustic signal that help to determine the size and location of the target object inside normal tissue. The analytical simulation used a spherical wave model representing target object (blood vessel or tumor) inside normal tissue. A computer program in MATLAB environment has been written to realize this simulation. This model generates time resolved acoustic wave signal that include both expansion and contraction parts of the wave. The photoacoustic signal from the target object is simulated for a range of laser pulse duration 10ns-10μs emitted from Nd:YAG laser, depth of target object 0.3-3 cm, distance from the object to the detector 0.7-3 cm and the diameter of target object 0.1-0.6 cm. The diameter of the object computed by the simulation is always being 75% of its value. The amplitude of the signal is directly proportional with the laser pulse energy and inversely proportional with the depth of target object and the distance from the object to the detector. The PA signal is fully generated in Nano second laser pulse duration range as it is short enough to fulfill the stress confinement condition.